European UNESCO Geoparks: Introduction to Part II - Michael Benton (Geoconservation Research)
The concept of the volume is to survey all the key geoparks throughout Europe in terms of their palaeontological significance. The second set of 36 articles in this Part cover the long span of geological time from the Triassic to the Quaternary, arranged in chronostratigraphic order. These document some of the most important stages in the history of life, especially focusing on life after the end-Permian mass extinction, as marine and terrestrial ecosystems rebuilt, and the ‘modern-style’ faunas and floras emerged.